The Effect of Biochar on Sulfate Desorption Kinetics by Selected Soil in Sudan Savanna, Nigeria - Murabbi Aliyu; Azare Isa Magaji; Nuhu Okomomi Isa; Saminu Abdulrahman Ibrahim; Abdu Nafiu (CV. Literasi Indonesia, 2023)
Biochar is regarded as a promising soil amendment that maximizes soil productivity to boost food security. Limited data is available on the influence of biochar on sulfate desorption behavior in soil. To fill the knowledge gap, this research attempts to investigate sulfate sorption and desorption kinetics with soil parent materials mixed with biochar. Understanding the effects is of great importance in selecting a fit diagnosis and fertilization of S to ensure sustainable crop production and environmental protection. Maize stalk biochar was prepared and used for the study. The variation between soil desorption data (with and without biochar) was examined using a two-way analysis of variance (ANOVA) with fully randomized designs (CRD). The results obtained showed that the studied Biochar (BC) had no significant (P = 0.05) impact on the release of adsorbing S, independent of time and soil constituents. The findings led to the conclusion that the rate of desorption of adsorbed sulfate desorption by the studied soil parent material is not primarily controlled by biochar. Therefore, it is recommended to test the compatibility of BC to release the adsorbed sulfur, before applying it as an amendment to the soil. Linking the practice of on-farm sulfur management to OM management is also recommended.